STRATEGI KOMUNIKASI ORANG TUA DENGAN ANAK DALAM RANGKA MEMAHAMI DAN MENGENDALIKAN PERKEMBANGAN ANAK (STUDI DI KOTA BATU) - Farid Rusman (Universitas Muhammadiyah Malang, 2019)
The development of children is very important to get serious attention, not only by their parents but also by society and state, because society and state are very concerned about the quality of children in its development until adulthood, to become human beings adult useful for society and for the country. In the context of the development of children into adulthood, children need certain treatment especially from those who are closest to them, that is their parents for their development always in healthy condition both physical, psychological and social. Thus interpersonal communication by parents with their children is important to be observed, to study, especially studies undertaken in order to understand and control the development of their children. From their understanding of the various communication strategies they perform, through this study, the researcher derived conclusions about which strategies are more suited to the need to gain an understanding of the development of the child's condition, and which strategies are appropriate to control the development of the children’s condition. Of the 10 cases studied, 5 subjects (cases) developed a swung carrot strategy, 3 cases using a hanging sword strategy, and only 2 cases that developed a catalyst strategy.